Analyzing Madeira and Bermuda as two different destinations: A text mining approach - Ferreira, E.S.; Loureiro, S. M. C.; Bilro, R.G.; Ferro, T. M. (Journal of Promotion Management, 2022)
This study explores how tourists perceive two island destinations (Madeira and Bermuda) through reviews on social network platforms. An Artificial intelligence data mining methodology is used (text mining) to address the research problem. Authors collected TripAdvisor reviews, 1148 from Madeira and 635 from Bermuda (total pool of 1783 reviews). A database with three coding was generated, based on literature: Tourism Experience Model (TEM), Membership Level of reviewers (ML) and Categories. Data was analyzed through Meaning Cloud software. Results point out an overall customer satisfaction regarding both islands, but slightly superior for Madeira’s island. This research also discusses reviewers ranking level, the type of language in use, and the generation of negative content. It is possible to conclude that reviews can persuade others, namely their booking intention.